iOS 8 app development with Swift - Deitel, Paul J.; Safari eBooks ([Place of publication not identified] : Prentice Hall : Pearson, 2016)
"In these two LiveLessons videos, Paul Deitel presents everything you need to know to become an expert iOS programmer using the Swift programming language. In Swift Fundamentals LiveLessons, Deitel teaches core Swift programming concepts through his signature "live code" approach. In iOS 8 App Development Fundamentals LiveLessons, Deitel uses an app-driven approach each new technology is discussed in the context of seven fully tested iOS 8 apps."--Resource description page.
Presenter, Paul Deitel.
Title from resource description page (viewed November 16, 2015).
Date of publication from title screen.
Keywords: iOS (Electronic resource); Application software -- Development; Swift (Computer program language); Electronic books